Digital Mission in a Post-Pandemic World: Reimagining Evangelism and Doscipleship - Kezia Meifa Supit; Michelle Johannis; Jeane Maisudu; Jeshinta Tarek (International Forum of Researchers and Lecturers, 2024)
The COVID-19 pandemic marked a significant turning point in the global church's approachto mission and ministry, particularly through the adoption of digital spaces. The rapid shift to digitalplatforms was not merely a practical adaptation but reflected a deeper transformation in how thechurch understands presence, community, and engagement in the world. This article aims to examinehow evangelism and discipleship practices have evolved in digital forms in the post-pandemic context,and to explore the theological and ethical implications of